Utilization of Rambai Fruit Vinegar (Baccaurea motleyana) as a Natural Fixator in Cotton Fabric Dyeing with Dayak Onion Bulb Extract (Eleutherine palmifolia (L.) Merr) - Tiara, Tiara; Masriani, Masriani; Hairida, Hairida (Universitas Pendidikan Mandalika, 2024)
The use of synthetic dyes in the textile industry has a negative impact on the environment. One solution that can overcome this impact is to switch to using natural dyes. However, natural dyes tend to produce less stable colors and fade easily. For this reason, a fixator is needed that can strengthen and maintain the natural dye in the fabric. Rambai fruit was chosen as a fixator because of the content of ascorbic acid which has the potential to be a natural fixator. This study aims to analyze the effect of the concentration of rambai fruit vinegar fixator on the dyeing of cotton fabrics with Dayak onion extract on color fastness. This research method is included in experimental research using the Î”E value as analysis data. Based on the results of the Î”E value, the concentration of 80% has the best level of color fastness. The results of the anova one-way test on the variation of the rambai fruit vinegar fixator obtained a significant result (p<0.05). This shows that there is an effect between the use of rambai fruit vinegar fixator concentration and color fading resistance using Dayak onion bulb extract. At a concentration of 80%, rambai fruit vinegar fixator is the most optimal concentration as a cotton fabric fixator with dye of Dayak onion bulb extract (Eleutherine palmifolia (L.) Merr) with a Î”E value of 3.47. Thus, rambai fruit vinegar with a high concentration can be an alternative fixator in the textile industry. This research contributes to the development of more environmentally friendly natural fixator materials in the textile industry that replace more harmful chemical fixators.